+0  
 
0
257
1
avatar

What is the value of  g(−3) when  g(x)=2x−2 ?

Guest Oct 10, 2017

Best Answer 

 #1
avatar+7339 
+1

g(x)  =  2x - 2

 

To find  g(-3) , replace every " x " with " -3 " and simplify.

 

g(-3)  =  2(-3) - 2

g(-3)  =  -6 - 2

g(-3)  =  -8

hectictar  Oct 10, 2017
 #1
avatar+7339 
+1
Best Answer

g(x)  =  2x - 2

 

To find  g(-3) , replace every " x " with " -3 " and simplify.

 

g(-3)  =  2(-3) - 2

g(-3)  =  -6 - 2

g(-3)  =  -8

hectictar  Oct 10, 2017

12 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.